The First Records of Pelagic Gastropods Species from the Celebes Sea, North Sulawesi, Indonesia - Ompi, Medy; Simbolon, Anna Rejeki; Rimper, Joice Rinefi Tavrita Sylvia Loura; Kaunang, Stella Tiny; Jensen, Kathe Rose (Journal of Fisheries and Environment, 2024)
Despite their weak swimming abilities, which prevent them from swimming against general ocean currents, gastropod larvae can still achieve widespread dispersal. This study aimed to identify pelagic gastropod species, both holoplanktonic and meroplanktonic, and to analyze their distribution in the Celebes Sea. Gastropods were sampled using an Isaacs-Kidd Midwater Trawl (IKMT) during the EWIN 2018 Cruise aboard the R.V. Baruna Jaya VIII LIPI. Species identification relied on morphology and DNA barcoding. Eight holoplanktonic gastropod species were identified: Atlanta inclinata (Atlantidae, Subclass Caenogastropoda), Creseis acicula, Creseis virgula, Boasia chierchiae, Styliola subula (Creseidae), Cavolinia labiata, Telodiacria sp. (Cavoliniidae), and Clio convexa (Cliidae), all belonging to Subclass Heterobranchia. The meroplanktonic species identified, all Caenogastropoda, included Reticutriton pfeifferianus (Cymatiidae), Dulcerana granularis (Bursidae), and Lampasopsis rhodostoma (Bursidae). Most species were found distributed across stations in the eastern and western parts of the Celebes Sea. With the exception of Creseis acicula, Styliola subula, and Reticutriton pfeifferianus, all identified species represent first records for the Celebes Sea. This study marks the first research in the Celebes Sea utilizing morphology and DNA barcoding for identifying pelagic gastropod species, providing a foundational dataset for future investigations.